SSR PRIMER SELECT AND ANALYSIS IN Malus Mill GENETIC RELATIONSHIP RESEARCH - L. H. Zuo; M. S. Yang; J. Zhang; H. Y. Liang (Journal of Animal and Plant Sciences, 2015)
Thirty pairs of polymorphism SSR primers were used for cluster analysis on 18 Xinjiang wild apple clones, 23 edible apple varieties, and 7 apple rootstock varieties. Forty eight varieties were classified into three groups: edible apple, Xinjiang wild apple, and rootstock apple, which do not interlace with each other. Varieties with genetic relationships were closely clustered inside the groups, consistent with the traditional family tree. This paper classified the primers into three types. The relevant analysis of the comprehensive cluster results of all primers indicated the second primer group had the best correlation, with the coefficient of 0.957, whereas the first premier group had the lowest correlation, with the coefficient of 0.871. The second primer group had better distinguishing ability for edible apple and rootstock apple; the third primer group had poor distinguishing ability for rootstock apple; the first primer group can be applied to distinguish Xinjiang wild apple. The cluster results of the combination of 6 highly-effective primers on 48 apple samples had the correlation coefficient of 0.940 with the comprehensive cluster results of 30 pairs of primers.
Keywords: Malus Mill; SSR marker; primer selection; primer efficiency